Complete Genome Sequence of Stenotrophomonas Phage Mendera - Garza, Kameron D. (Microbiol Resour Announc, 2020)
Stenotrophomonas maltophilia is an emerging opportunistic human pathogen. In this report, we describe the isolation and genomic annotation of the S. maltophilia-infecting bacteriophage Mendera. A myophage of 159,961 base pairs, Mendera is T4-like and related most closely to Stenotrophomonas phage IME-SM1.